Comparison of Clinical Efficacy of Intravenous Acetaminophen with Intravenous Morphine in Acute Renal Colic: A Randomized, Double-Blind, Controlled Trial - Masoumi, Kambiz; Forouzan, Arash; Asgari Darian, Ali; Feli, Maryam; Barzegari, Hassan; Khavanin, Ali (Emergency Medicine International, 2014)
The aim of this study was to compare the clinical efficacy of intravenous acetaminophen with intravenous morphine in acute renal colic pain management. In this double-blind controlled trial, patients aged 18–55 years, diagnosed with acute renal colic, who met the inclusion and exclusion criteria, were randomized into two groups. First, using the visual analogue scale (VAS), intensity of pain was assessed in both groups. Then, one gram of intravenous acetaminophen or 0.1 mg/kg morphine was infused in 100 mL normal saline to either acetaminophen or morphine group. Intensity of pain was reassessed in 15, 30, 45, and 60 minutes according to VAS criteria. Finally, data from 108 patients were analyzed, 54 patients in each group. No significant difference was observed between the two groups in regard to sex (P=0.13), mean age (P=0.54), and baseline visual analogue score (P=0.21). A repeated measure analysis of variance revealed that the difference between the two treatments was significant (P=0.0001). The VAS reduction at primary endpoint (30 min after drug administration) was significantly higher in the acetaminophen group than in the morphine group (P=0.0001). This study demonstrated that intravenous acetaminophen could be more effective than intravenous morphine in acute renal colic patients’ pain relief.